COHERENCE ANALYSIS OF RACIAL PREJUDICE IN THE ANSWERS TO QUORA APPLICATIONâ€™S QUESTION WHAT IS THE MOST RACIST THING SOMEONE HAS SAID TO YOU - Saraswati Putri, Sang Ayu Dian; Resen, I Wayan; Karya, I Wayan Sidha (LITERA : Jurnal Bahasa Dan Sastra, 2022)
ABSTRACTThis study aims to analyze the coherence of answers by Quora application users thatcontain racist utterances. Answers from Quora users were analyzed for racial prejudicebased on the theory from Blummer (1958) about feelings of empathy that represent racialprejudice. The four feelings referred to by Blummer (1958) are: feeling superior, feelingthat the subordinate race is essentially different, the feeling of claiming ownership ofspecial rights, and the fourth is that the subordinate race has hidden motives for the specialrights of the dominant race. To analyze the coherence of user answers, the theory used isthe theory proposed by Oshima & Hogue (2006) about four ways of achieving coherence.According to Oshima & Hogue (2006), there are four ways to achieve coherence, namely:repeating keywords, using pronouns consistently, using transitional signs, and arrangingideas in a logical order. The result indicates that from the five analyzed data points, fourcan be classified as the feeling of the subordinate group is different and alien, and onecan be identified as the feeling of superiority. The answers are considered as coherence,the writers manage to make a repetition of the key noun, using consistent pronouns, usingtransition signals, and arranging the ideas in logical order.Keywords: coherence, racism, discourse and racism, racial prejudiceABSTRAKPenelitian ini bertujuan untuk menganalisis koherensi dari jawaban para penggunaaplikasi Quora yang mengandung ujaran-ujaran rasisme. Jawaban dari para penggunaQuora akan dianalisis dari sisi prasangka rasial berdasarkan teori dari Blummer (1958)tentang empat perasaan yang mewakili prasangka rasial. Adapun empat perasaan yangdimaksud oleh Blummer (1958) yaitu: perasaan superior, perasaan bahwa ras bawahanpada hakikatnya berbeda, perasaan pernyataan kepemilikan atas hak-hak istimewakhusus, dan yang keempat adalah bahwa ras bawahan mempunyai motif terselubungterhadap hak khusus dari ras dominan. Untuk menganalisis koherensi dari jawabanpengguna, teori yang digunakan adalah teori koherensi oleh Oshima & Hogue (2006)tentang empat cara mencapai koheren. Menurut Oshima & Hogue (2006) ada empat carauntuk bisa mencapai koherensi yaitu: mengulang kata kunci, menggunakan kata gantisecara konsisten, menggunakan tanda-tanda transisi, dan merangkai ide dengan urutanyang logis. Hasil penelitian ini menunjukkan, dari lima data yang telah dianalisis, empatdapat diklasifikasikan sebagai perasaan bahwa ras bawahaan pada hakikatnya berbeda,dan satu teridentifikasi sebagai perasaan superior. Jawaban pada penelitian inidianggap koheren, diÂ  mana para penlis mampu untuk mengulang kata kunci, menggunakan kata ganti secara konsisten, menggunakan tanda-tanda transisi, sertamerangkai ide dengan urutan yang logis.Kata Kunci: koherensi, rasisme, wacana dan rasisme, prasangka rasial